Cellular Stress Response Gene Expression During Upper and Lower Body High Intensity Exercises. - Andrzej Kochanowicz; Stanisław Sawczyn; Bartłomiej Niespodziński; Jan Mieszkowski; Kazimierz Kochanowicz; Małgorzata Żychowska (PLoS ONE)
Objectives The aim was to compare the effect of upper and lower body high-intensity exercise on chosen genes expression in athletes and non-athletes. Method Fourteen elite male artistic gymnasts (EAG) aged 20.6 ± 3.3 years and 14 physically active men (PAM) aged 19.9 ± 1.0 years performed lower and upper body 30 s Wingate Tests. Blood samples were collected before, 5 and 30 minutes after each effort to assess gene expression via PCR. Results Significantly higher mechanical parameters after lower body exercise was observed in both groups, for relative power (8.7 ± 1.2 W/kg in gymnasts, 7.2 ± 1.2 W/kg in controls, p = 0.01) and mean power (6.7 ± 0.7 W/kg in gymnasts, 5.4 ± 0.8 W/kg in controls, p = 0.01). No differences in lower versus upper body gene expression were detected for all tested genes as well as between gymnasts and physical active man. For IL-6 m-RNA time-dependent effect was observed. Conclusions Because of no significant differences in expression of genes associated with cellular stress response the similar adaptive effect to exercise may be obtained so by lower and upper body exercise.